Sundarbans - Ganguly, D. K. (Indian Forester, 1965)
Distribution of various species growing in the Sundarbans, their characteristics and utilization are discussed. Methods of collection of honey and wax are described. The system of management of forests and the modes of extraction are described. The article records author’s personal study of the various forestry problems in the Sundar bans and some of the solutions to these.